Comparative Study of Duodenal Histology in Three Type of Birds and Two Different Rations - Israa Badi Khalaf (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The avian duodenum is the primary site of enzymatic digestion and nutrient absorption, and its morphology reflects dietary specialization and metabolic demands. Specific Background: Passerine birds such as the Canary (Serinus canaria), Zebra Finch (Taeniopygia guttata), and White-eared Bulbul (Pycnonotus leucotis) exhibit distinct feeding habits, including granivory and frugivory/insectivory, which may be associated with differences in duodenal microarchitecture. Knowledge Gap: Comparative histomorphological data on the duodenum of these small passerines remain limited. Aims: This study aimed to compare the gross morphology, histological organization, and morphometric characteristics of the duodenum in the three species. Results: In all species, the duodenum formed a characteristic U-shaped loop surrounding the pancreas and consisted of four tunicae: mucosa, submucosa, muscularis, and serosa. The muscularis mucosa was absent in all birds. The White-eared Bulbul showed the greatest mucosal thickness and the highest goblet cell ratio (33.1%), whereas the Canary exhibited the longest villi and the thickest tunica muscularis. The Zebra Finch had the lowest mucosal thickness and shortest villi. Crypt depth was greatest in the Bulbul and Zebra Finch. Novelty: This study demonstrates species-specific duodenal histological patterns linked to contrasting dietary strategies in three passerine birds. Implications: These findings provide baseline anatomical and histological data that improve understanding of digestive adaptation and support future comparative and veterinary investigations in avian species. Highlights: • All species exhibited a U-shaped duodenal loop enclosing the pancreas and lacked muscularis mucosa.• White-eared Bulbul had the highest goblet cell proportion and greatest mucosal thickness.• Canary showed the longest villi and the thickest tunica muscularis among the examined birds. Keywords: Avian Duodenum, Comparative Histology, Passerine Birds, Goblet Cells, Digestive Adaptation